INTEGRITAS AUDITOR SEBAGAI PEMODERASI PENGARUH KOMPETENSI DAN INDEPENDENSI PADA KUALITAS AUDIT - Pitaloka, Yuli; Widanaputra, A.A.G.P (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
This study aimed to determine the effect of competence and independence of the auditor integrity as moderating the public accounting firm in the province of Bali. Sampling technique used in this research is purposive sampling with the number of samples obtained as many as 56 samples. Data collection methods used in this study was a questionnaire, which is distributed questionnaires to the auditor in public accounting firm. The data analysis technique used to test the hypothesis in this study is Moderated Regression Analysis (MRA). Based on the results obtained show that the effect on the competence and independence of audit quality. This shows that increasing the competence and independence of the audit quality is increasing. The results also showed that the integrity of the auditor able to moderate influence on the independence of audit quality, but are not able to moderate influence on the quality of audit competencies.
Keywords: Audit Quality, Competence, Independence, Integrity Auditor